Viral persistence and disease: cytopathology in the absence of cytolysis. - de la Torre, J; Borrow, P; Oldstone, M (1991)
Realising that viruses could persist and thereby cause chronic disease has been one of the major accomplishments in virology. In this review we will discuss the principles by which viruses can persist and how such persistence can lead to disease. Our focus will be on the ability of certain viruses to interfere subtly with the cell's ability to produce specific differentiated products as hormones, neurotransmitters, cytokines and immunoglobulins, etc., in the absence of their ability to lyse the cell they infect. By this means viruses can replicate in histologically normal appearing cells and tissues. Despite viral replication the infected cell maintains its normal anatomic architecture and yet the virus disorders the differentiated or luxury function of the cell leading to disturbances in homeostasis and disease. Viruses by this means likely underline a wide variety of clinical illnesses, currently of unknown aetiology, that affect the endocrine, immune, nervous and other differentiated systems.